Analisis Pengelolaan Keuangan Badan Usaha Milik Desa (BUMDes) di Desa Tombulang Timur Kecamatan Pinogaluman Kabupaten Bolaang Mongondow Utara - Ahmad, Aristia Rahayu N.; Amaliah, Tri Handayani; Husain, Siti Pratiwi (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aims to determine the financial management of the Village-Owned Enterprise (BUMDes) "Harapan Baru" in Tombulan Timur Village, Pinogaluman District, North Bolaang Mongondow Regency. This type of research is qualitative research that is descriptive in nature. The data sources used in this study are primary data and data collection techniques of observation, interviews and documentation. With the data analysis method, namely collecting data, analysis and conclusions. Based on the results of the study, it shows that the financial management of BUMDes Harapan Baru is still simple, the planning carried out by BUMDes Harapan Baru by holding meetings to form RAB, the implementation is carried out by the treasurer with receipts as proof of disbursement of funds, the recording carried out by the treasurer is still general, the accountability carried out by BUMDes Harapan Baru is by providing reports to the BPD and submitted to the community during the village deliberation once a year, the supervision carried out by the BUMDes is appropriate, namely by providing financial reports from the BUMDes to the village BPD, and the BPD has come to supervise.